A Study on the Recent Trends and Challenges with Special Reference to India in Modern Operation Management (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Production is a very important functional area in management. It  has a very crucial place in every industrial organization. Opera tion management deals with the production of goods and services  that people buy and use every day. Operation management deals  with decision making in the production function. The trends in operation management are never fads. They have  very good reasons to be in existence. They incorporate a lot of  lessons from the past and can affect the future in several ways  (Nersesian, 2000). From the industrial revolution in 1769 up to  the recent internet revolution, Operation management has seen  trends, which designed and redesigned the processes in order to make them more efficient, and business more profitable.This paper will focus on a very few of such recent trends which  have come up as the need of the hour and will dictate the future  of the businesses. Further the paper discuss how just in time or  lean management and supply chain management influences all  other trends popular in the field of operations management at the  moment. This makes an interesting study as to how operations  management has evolved in the face of changing businesses and  the recent trends gives a very clear idea about what to expect in  the near future, with respect to operations management.The paper also touches upon relevant aspects of the case of Toy ota, which have affected the way we see operations management  today.
Keywords: Production; Challenges; Modern Operation Management